Helicobacter pylori CheZHP and ChePep form a novel chemotaxis‐regulatory complex distinct from the core chemotaxis signaling proteins and the flagellar motor. Issue 6 (4th July 2015) - Lertsethtakarn, Paphavee; Howitt, Michael R.; Castellon, Juan; Amieva, Manuel R.; Ottemann, Karen M.
Summary Chemotaxis is important for Helicobacter pylori to colonize the stomach. Like other bacteria, H. pylori uses chemoreceptors and conserved chemotaxis proteins to phosphorylate the flagellar rotational response regulator, CheY, and modulate the flagellar rotational direction. Phosphorylated CheY is returned to its non‐phosphorylated state by phosphatases such as CheZ. In previously studied cases, chemotaxis phosphatases localize to the cellular poles by interactions with either the CheA chemotaxis kinase or flagellar motor proteins. We report here that the H. pylori CheZ, CheZHP, localizes to the poles independently of the flagellar motor, CheA, and all typical chemotaxis proteins. Instead, CheZHP localization depends on the chemotaxis regulatory protein ChePep, and reciprocally, ChePep requires CheZHP for its polar localization. We furthermore show that these proteins interact directly. Functional domain mapping of CheZHP determined the polar localization motif lies within the central domain of the protein and that the protein has regions outside of the active site that participate in chemotaxis. Our results suggest that CheZHP and ChePep form a distinct complex. These results therefore suggest the intriguing idea that some phosphatases localize independently of the other chemotaxis and motility proteins, possibly to confer unique regulation on these proteins' activities.